PENGEMBANGAN MEDIA PEMBELAJARAN AQUABUMI BERBASIS ARTICULATE STORYLINE MATERI SIKLUS AIR PADA MATA PELAJARAN IPAS KELAS V SDN 1 LIMBANGAN - Sajad, Ahmad; Azizah, Mira; Arisyanto, Prasena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low utilization of technology-based learning media in IPAS learning, particularly the Water Cycle topic in grade V at SDN 1 Limbangan, where teachers predominantly used printed books, resulting in low student comprehension. To address this challenge and foster 21st-century skills, the Aquabumi learning media was developed using Articulate Storyline, Design ed to be interactive, engaging, and relevant to educational technology. The study employed a Research and Development (R&D) method with the ADDIE model (Analyze , Design , Development , Implement, Evaluate). Data were collected through observations, needs questionnaires, interviews, expert validation (media and material), and teacher and student response questionnaires, involving 16 grade V students and the class teacher. Results showed Aquabumi was highly valid and practical, with media expert validation scoring 92% and material expert validation 90.6% (“Highly Valid” category). Teacher responses reached 90.6% and student responses 88.17%, both in the “Very Good” category. The media was considered attractive, easy to use, and significantly improved students’ motivation and understanding of the Water Cycle material. It is recommended that students use Aquabumi for independent learning, while teachers adopt it as an alternative IPAS teaching tool. Future Development s should expand content coverage, add interactive features such as simulations and educational games, and apply it to other subjects or levels to broaden and adapt its benefits.